2017
DOI: 10.1016/j.biocel.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Expression and alternative splicing of the cyclin-dependent kinase inhibitor-3 gene in human cancer

Abstract: The cyclin-dependent kinase inhibitor-3 (CDKN3) gene encodes a dual-specificity protein tyrosine phosphatase that dephosphorylates CDK1/CDK2 and other proteins. CDKN3 is often overexpressed in human cancer, and this overexpression correlates with reduced survival in several types of cancer. CDKN3 transcript variants and mutations have also been reported. The mechanism of CDKN3 overexpression and the role of CDKN3 transcript variants in human cancer are not entirely clear. Here, we review the literature and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…Cyclin-dependent kinase inhibitor 3 (CDKN3) serves crucial roles in the cell cycle and proliferation (8)(9)(10). CDKN3 performs its functions by binding to cyclin proteins, which results in dephosphorylation of CDK1 and CDK2 proteins and inhibition of cell cycle progression (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclin-dependent kinase inhibitor 3 (CDKN3) serves crucial roles in the cell cycle and proliferation (8)(9)(10). CDKN3 performs its functions by binding to cyclin proteins, which results in dephosphorylation of CDK1 and CDK2 proteins and inhibition of cell cycle progression (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been revealed that lncRNAs can increase or inhibit the expression levels of target genes to exert effects in cancer progression (24). CKIs are known to be critical tumor suppressors in various cancers and play key roles in cell cycle regulation (10,22,28) Importantly, CKIs are involved in the biological role of lncRNAs (28,39,40). The abnormal methylation in promoter regions of CKIs leads to gene expression inhibition, thus contributing to alteration of cell cycle (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase inhibitors (CKIs) are known to modulate cell cycle progression and function as tumor suppressors (21,22). p21 is an essential member of CKIs family, which includes p15, p16, p27 and p57 (21).…”
Section: Long Non-coding Rna Mlk7-as1 Promotes Proliferation In Humanmentioning
confidence: 99%
“…To identify the DAS events, we performed DAS analysis 57,58,59,60,61 . Briefly, the raw RNA-Seq reads first were aligned to mouse genome (mm9) using STAR 62 with default settings, and those uniquely mapped reads were retained to calculate the counts of the reads for each exon and each exon-exon junction annotated in the UCSC knownGene (mm9) table 63 using the Python package HTSeq 64 .…”
Section: Das Analysis Using Rna-seq Datamentioning
confidence: 99%